2016
DOI: 10.3389/fmicb.2016.00075
|View full text |Cite
|
Sign up to set email alerts
|

The Guaymas Basin Hiking Guide to Hydrothermal Mounds, Chimneys, and Microbial Mats: Complex Seafloor Expressions of Subsurface Hydrothermal Circulation

Abstract: The hydrothermal mats, mounds, and chimneys of the southern Guaymas Basin are the surface expression of complex subsurface hydrothermal circulation patterns. In this overview, we document the most frequently visited features of this hydrothermal area with photographs, temperature measurements, and selected geochemical data; many of these distinct habitats await characterization of their microbial communities and activities. Microprofiler deployments on microbial mats and hydrothermal sediments show their steep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
132
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 72 publications
7
132
0
Order By: Relevance
“…Acetate was the most abundant VFA (Figures g–l), and its concentration reached up to 229 μM (Dive 4871‐1, hot Northern Towers mat; Figure j). These concentrations were similar to previous reports for Guaymas Basin sediment (McKay et al, ; Teske et al, ), and comparable to values observed in subseafloor sediments (e.g., northern Cascadia Margin; Heuer et al, ). While acetate increased with depth at the Aceto Balsamico site, a subsurface maximum of >100 μM acetate was observed at the Northern Towers mats that were dominated by white Beggiatoa .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Acetate was the most abundant VFA (Figures g–l), and its concentration reached up to 229 μM (Dive 4871‐1, hot Northern Towers mat; Figure j). These concentrations were similar to previous reports for Guaymas Basin sediment (McKay et al, ; Teske et al, ), and comparable to values observed in subseafloor sediments (e.g., northern Cascadia Margin; Heuer et al, ). While acetate increased with depth at the Aceto Balsamico site, a subsurface maximum of >100 μM acetate was observed at the Northern Towers mats that were dominated by white Beggiatoa .…”
Section: Resultssupporting
confidence: 91%
“…sediment (McKay et al, 2012;Teske et al, 2016), and comparable to values observed in subseafloor sediments (e.g., northern However, acetate constituted up to 11% of bulk DOC in Northern Towers-1 sediment and lactate accounted for >12% of DOC in the low organic carbon mat at Ultra Mound.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Previous work in Guaymas Basin has shown that oxygen is quickly consumed at the sediment–water interface such that sediments become anoxic within the upper few millimetres (Winkel et al ., ; Teske et al ., ) and are dominated by microbial groups involved in the anaerobic oxidation of methane, sulphate reduction and anaerobic degradation of hydrocarbons (Teske et al ., ; Dhillon et al ., ; Biddle et al ., ; McKay et al ., ; Dowell et al ., ; Dombrowski et al ., , ).…”
Section: Methodsmentioning
confidence: 97%
“…Several studies have further addressed the potential microbial habitats beneath the seafloor hydrothermal vents, the so-called 'sub-vent biosphere', and have indicated the possible occurrence of functionally active and metabolically diverse (hyper-)thermophilic microbial communities associated with shallow subseafloor hydrothermal fluids and mineral deposits (Deming and Baross, 1993;Delaney et al, 1998;Summit and Baross, 1998;Huber et al, 2002Huber et al, , 2003. The compositions and functions of the sub-vent microbial communities have been inferred from culture-dependent and culture-independent analyses of microbial communities in (i) in situ growth chambers placed in hydrothermal fluid flows (Karl et al, 1988;Reysenbach et al, 2000;Corre et al, 2001;Takai et al, 2004), (ii) crustal fluids collected directly from the shallow subseafloor environments (~10 m below the seafloor [mbsf]) via seafloor drilling or probe insertion (Cowen et al, 2003;Higashi et al, 2004;Huber et al, 2006;Kato et al, 2009;Orcutt et al, 2011), (iii) hydrothermal sediments (Teske et al, 2002;Dhillon et al, 2005;Nunoura et al, 2010;Teske et al, 2014;Dowell et al, 2016;Teske et al, 2016) and (iv) chimney structures of active hydrothermal vents (Takai et al, 2001;Schrenk et al, 2003;Nakagawa et al, 2005). These studies found that mesophilic, thermophilic and hyperthermophilic members of Epsilonproteobacteria, Gammaproteobacteria, Aquificales, Thermococcales and Methanococales were the potentially predominant microbial components in the sub-vent biosphere.…”
Section: Introductionmentioning
confidence: 99%